TINDAK KEKERASAN DALAM NOVEL LAILUN WA QUDHBAAN KARYA NAJIB KAILANY (Kajian Strukturalisme Genetik) - Zaka, Muhammad Qodhi; Dayudin, Dayudin (Hijai - Journal on Arabic Language and Literature, 2019)
This research examines the forms of violence and factors underlying the acts of violence in the novel Lailun wa Qudhbaan by Najib Kailany. The purpose of this study is to find out the forms of violence and factors underlying the acts of violence in the novel Lailun wa Qudhbaan by Najib Kailany. The method used in this reaserch is a descriptive analysis method with a study of genetic structuralism. This study uses structural genetic theory to reveal all forms of violence and the factors behind violence based on life experiences experienced by the author.Keywords: Violence, Novel Lailun wa Qudhbaan, Genetic Structuralism, by reading it off.